Incidence, Gross Morphology, Histopathology and Immunohistochemistry of Canine Mammary Tumors - Patel, MP; Ghodasara, DJ; Raval, SH; Joshi, BP (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The aim of present investigation was to study the gross morphology and incidence of canine mammary tumors (CMTs) based on age,  sex, breed, reproductive status and location along with histopathological classification and immunohistochemical characteristics. A  total of 56 CMTs samples were collected from 49 cases of dogs. Gross morphology was studied in 26 cases of canine mammary tumors.  For histopathological classification, samples were fixed in 10% formalin, embedded in paraffin and sections (5 µm thick) obtained from  each was stained with H&E stain. Immuno-histochemistry was carried out by using p63 antibody to confirm the histopathological types  of CMTs. Malignant tumors and benign tumors were mostly observed in older dogs. Among 9 breeds affected, the highest incidence  was recorded in a German shepherd. Caudal abdominal pair was most commonly affected. Most of the cases were observed in intact  female dogs, except for one male dog. The tumors were oval and round in shape with 30–2000 g weight, soft to hard in consistency and  grayish white cut surface. Out of 56 CMTs, the highest incidence was found of malignant neoplasms (36/56, 64.28%), followed by benign  neoplasms (10/56, 17.85%) and non-neoplastic proliferation hyperplasia/dysplasia (10/56, 17.85%). Complex carcinoma, carcinoma, and  malignant myoepithelioma and malignant myoepithelioma were confirmed by p63 antibody. In these neoplasms, myoepithelial cells  showed strong immunoreactivity with p63.
Keywords: Canine mammary tumor; Incidence; Gross morphology; Histopathology; Immunohistochemistry